PS 16-19 EVALUATION OF ARTERIAL STIFFNESS IN ELDERLY WITH PRE-HYPERTENSION. (September 2016) - Agarwal, Shivika; Khurana, Tariq; Pandey, Anil Kumar
Abstract : Objective: To find out the potential of indices of arterial stiffness in risk stratification and the need to introduce such measures into clinical practice. Design and method: A cross sectional study was conducted on elderly subjects aged 60–80 years with prehypertension (n = 35) and age matched normotensives (n = 30). We measured PWV (Pulse Wave Velocity) by Periscope™.The arterial stiffness was assessed by measuring (1) Pulse Wave Velocity between carotid-femoral (c-f PWV) and brachial ankle (b-aPWV) (2) Augmentation Index (AIx) (3) Arterial Stiffness Index (ASI) at brachial (bASI) and tibial artery (aASI). Results: We found a significant increase in c-f PWV (p < 0.001), b-aPWV (p < 0.001) and AIx @75%(p < 0.001) in prehypertensives than normotensive elderly individuals. There was no significant difference in the ASI at brachial and tibial arteries. The significant predictor of c-f PWV and AIx@75 (%) was Systolic BP, and aASI was Pulse pressure (PP). Conclusions: These findings show an augmentation of age related arterial stiffness in elderly with prehypertension.The Aortic Pulse Wave Velocity reflects central arterial stiffness. Aortic Pulse Wave Velocity predicted Cardiovascular outcomes over and beyond BP and traditional risk factors.